2017
DOI: 10.1021/acsami.7b05209
|View full text |Cite
|
Sign up to set email alerts
|

Light-Induced Proton Pumping with a Semiconductor: Vision for Photoproton Lateral Separation and Robust Manipulation

Abstract: Energy-transfer reactions are the key for living open systems, biological chemical networking, and the development of life-inspired nanoscale machineries. It is a challenge to find simple reliable synthetic chemical networks providing a localization of the time-dependent flux of matter. In this paper, we look to photocatalytic reaction on TiO from different angles, focusing on proton generation and introducing a reliable, minimal-reagent-consuming, stable inorganic light-promoted proton pump. Localized illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…That is, water splitting on a semiconductor can cause the formation of H + and/or OH À . We recently studied, in detail, the process of water splitting on a titania surface 17 focusing on H + and OH À (not H 2 and O 2 as usual (note, that there is no obvious gas bubbling in our system)) and we observed that this process leads to a pronounced local surface acidification of the irradiated surface and subsequent pH change. The overall pH does not change, although, a pH gradient on the surface may exist.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…That is, water splitting on a semiconductor can cause the formation of H + and/or OH À . We recently studied, in detail, the process of water splitting on a titania surface 17 focusing on H + and OH À (not H 2 and O 2 as usual (note, that there is no obvious gas bubbling in our system)) and we observed that this process leads to a pronounced local surface acidification of the irradiated surface and subsequent pH change. The overall pH does not change, although, a pH gradient on the surface may exist.…”
Section: Introductionmentioning
confidence: 93%
“…The overall pH does not change, although, a pH gradient on the surface may exist. 17 Thus the inorganic surface and its nanostructuring may be involved in the reaction through process location (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the light‐induced has strong influence on water‐splitting process in semiconductor materials. Maltanava et al and Ulasevich et al independently introduced the layer‐by‐layer assembly of metal NPs using inorganic TiO 2 materials. Upon UV laser irradiation, they found that the photoactivity of semiconductor materials has strong influence on pH change because of i) the photocatalytic reaction of water splitting, ii) electrochemical process, iii) chemical or biochemical reaction network, and iv) biological process.…”
Section: Factors Affecting Photoactivity Of Spr‐assisted Semiconductorsmentioning
confidence: 99%
“…Notably, the TiO 2 /PSS/PEI film shows much lower photocurrent than TiO 2 one. We propose that the surface states responsible for photoactivation might be the surface states associated with the acidification at the titania surface . It is known that PEI has proton sponge ability .…”
Section: Figurementioning
confidence: 99%
“…On the contrary, having the same photoactivity center (TiO 2 ), it doesn't happen for the system of TiO 2 /PSS/PEI. It should also be noted that the presence of a proton on TiO 2 was shown by us before as well as efficient pH‐buffering of 2 nm chitosan layer …”
Section: Figurementioning
confidence: 99%